F.B. Sanborn correspondence and essays - Sanborn, F. B. (Franklin Benjamin), 1831-1917.
College essays and correspondence with Octavius Brooks Frothingham and Gerrit Smith. Correspondence with Frothingham concerns his biography of Smith.
In part, handwritten transcripts of correspondence.
Author and journalist.
Collection material in English.
Keywords: Smith, Gerrit, -- 1797-1874.; Smith, Gerrit, -- 1797-1874 -- Correspondence; Frothingham, Octavius Brooks, -- 1822-1895 -- Correspondence; Authors; Journalists